2004
DOI: 10.1128/aac.48.7.2766-2770.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Iodonium Salts against Oral and Dental Anaerobes

Abstract: The comparative in vitro activities of 11 iodonium salt compounds, 0.12% chlorhexidine, and four antimicrobial agents against 322 anaerobic and fastidious potential dental and periodontal bacterial pathogens were studied. Iodonium salts 3, 4, 5, 9, and 10 had in vitro activities comparable to that of chlorhexidine against most isolates. These compounds may be suitable for incorporation into an oral mouthwash.Biodiversity studies of subgingival plaque estimate that more than 400 different species may colonize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…On the other hand, there are only fragmented reports on the biological activity of diaryliodonium salts [ 44 49 ]. Goldstein et al [ 45 ] and Doroshow et al [ 46 ] reported that some diaryliodonium salts show effective antimicrobial and NOX inhibitor activity, respectively. Several aryliodonium salts, aryliodonium ylides, and (diacyloxyiodo)arenes were also examined for their antibacterial activities against ice nucleation active Pseudomonas syringae, and aryliodonium salts, especially those with electron-withdrawing groups, exhibit higher antibacterial activities [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are only fragmented reports on the biological activity of diaryliodonium salts [ 44 49 ]. Goldstein et al [ 45 ] and Doroshow et al [ 46 ] reported that some diaryliodonium salts show effective antimicrobial and NOX inhibitor activity, respectively. Several aryliodonium salts, aryliodonium ylides, and (diacyloxyiodo)arenes were also examined for their antibacterial activities against ice nucleation active Pseudomonas syringae, and aryliodonium salts, especially those with electron-withdrawing groups, exhibit higher antibacterial activities [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bearing two benzene rings as the hydrophobic moiety, the synthesized hypervalent iodine salts would disrupt bacterial cell membrane in the same manner, causing the disintegration of the cell membrane, leakage of cytoplasmic components, and subsequent death. The introduction of a long ether chain has not only enhanced the hydrophilicity of the diaryliodonium salts resulting in a better hydrophilic–lipophilic balance (Goldstein et al, ) but also facilitated the interaction between the amphiphilic molecule and bacterial cell membrane via the formation of hydrogen bonds. As suggested by the structural descriptors predicting antiseptic efficacy summarized in Cronin et al’s () work, hydrogen bonds help to strengthen the interaction between antibacterial compounds and the outer cell membrane, further contributing to enhanced antibacterial efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…We have used three synthetic routes to obtain 19 diaryliodonium salts, and all of them gave high yield, ideal purity, and easy handling (Bielawski et al, ; Matsuzaki et al, ; Petersen et al, ). To address the poor water solubility issue of the fluorinated diaryliodonium salts (Goldstein et al, ), a long ether chain containing three ethoxy groups was added to one of the benzene rings of the scaffold. The purity of the 19 diaryliodonium salts was roughly determined by the experimental phenomenon that only one spot was observed on thin layer chromatography (TLC) measurements when using various developing solvents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations